Application of nano pigments in inkjet paper coating - (:unkn) unknown (My University, 2010)
Coated inkjet paper is one of essential factors that dominate inkjet print quality. Coating pigments are the most abundant component that impacts coating layer performance. In high-end coated inkjet paper, fumed silica is the primary pigment in coating formulations, because of its ideal ink absorption and optical appearance. Other pigments have also been widely introduced into silica coating colors. In this study, two nano scale pigments, clay and ground calcium carbonate, were added into a commercial inkjet coating formulation respectively. Meanwhile, two conventional pigments, #1 clay and precipitated calcium carbonate were applied into the formulation as references. All of the formulations were coated paper and paperboard base sheets via a cylindrical laboratory coater. A systematic evaluation has been applied including paper surface conditions, optical properties and printability. These two nano scale pigments were found to increase optical and print performance. Specifically, the nano clay was expected to replace polyethylene layers of premium inkjet paper.